Suture Button Fixation Treatment of Chronic Lisfranc Injury in Professional Dancers and High-Level Athletes. Issue 4 (December 2015) - Charlton, Timothy; Boe, Chelsea; Thordarson, David B.
Chronic Lisfranc injury is a subtle and severe injury in high-level athletes, including dancers. This patient population is generally intolerant of intra-articular screw fixation and can develop significant post-traumatic arthritis with potentially career ending complications. Flexible fixation with suture-button devices provides potential restoration of physiologic motion at the joint, with appropriate support for healing that may facilitate return to en pointe activities for dancers. We hypothesized that the suture-button device would restore motion at the Lisfranc joint and allow for return to activities in this particular population without the limitations and complications of rigid fixation. We operated on seven dancers and high-level athletes with diagnosed Lisfranc injuries by installing a suture-button device. All patients had failed conservative management after late presentation. They were allowed to return to sport in 6 months, preoperative and postoperative American Orthopaedic Foot and Ankle Score (AOFAS) foot scores were obtained, and patients were followed for a minimum of 15 months. All seven returned to full activities in 6 months, with radiographic evidence of fixation and no complications to date. AOFAS foot scores improved from an average of 65 preoperatively to an average of 97 postoperatively at latest follow-up. It is concluded that flexible fixation with suture-button type device represents a viable alternative to screw fixation or fusion that may allow dancers and athletes to return to previous levels of activity after Lisfranc injury. This case series represents to our knowledge the first application of this device to a unique population that requires flexibility at the Lisfranc joint for performance.